2018
DOI: 10.1177/1091581818773979
|View full text |Cite
|
Sign up to set email alerts
|

Skin and Eye Irritation Assessment of Oil Palm (Elaeis guineensis) Leaf Extract for Topical Application

Abstract: Many types of phytochemicals have been found to be present in oil palm leaf and could potentially be used as functional ingredients for skincare product. However, as of today, there is no published report on hazard identification and safety assessment of oil palm ( Elaeis guineensis) leaf extract (OPLE), particularly on skin and eye irritation. In this study, potential hazard of OPLE on skin and eye irritation was evaluated as an initial step to the safety assessment of OPLE. In vitro cell viability study of O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In the in vitro toxicity test with BSLT oil palm leaf extract showed an LC50 value of 9,00 and 3,87 mg/mL at 6 and 24 hours of observation which showed that the oil palm leaf extract was not toxic [8]. In a study conducted by [9], it showed that palm leaf extract in vitro at concentrations of 1%, 5% and 10% did not cause irritation to the eyes and skin.…”
Section: Introductionmentioning
confidence: 96%
“…In the in vitro toxicity test with BSLT oil palm leaf extract showed an LC50 value of 9,00 and 3,87 mg/mL at 6 and 24 hours of observation which showed that the oil palm leaf extract was not toxic [8]. In a study conducted by [9], it showed that palm leaf extract in vitro at concentrations of 1%, 5% and 10% did not cause irritation to the eyes and skin.…”
Section: Introductionmentioning
confidence: 96%
“…This study addresses the effects of comfrey herb cream on skin regeneration in a 3-dimensional human skin model of reconstructed human epidermis (RhE). RhE models are commercially available and typically used in skin studies [21] including studies using imaging techniques [22], especially in studies related to skin irritation as a replacement of animal experiments [23]. The RhE model is even recommended for the official OECD test method No.…”
Section: Introductionmentioning
confidence: 99%
“…These compounds are recognized for their potency as antioxidants, anti-mutagenic, antiinflammatory and anti-cancer agents, as well as several other nutritional and health benefits [11][12]. Other bioactive ingredients exhibiting anti-tyrosinase and antimicrobial activities are also present in the OPLE, whereas certain compounds can protect the human skin against ultraviolet (UV) radiation, implying their usability for topical application [13]. Specifically, catechins viz.…”
Section: ■ Introductionmentioning
confidence: 99%